PENGARUH KEMUDAHAN PENGGUNAAN, PROMOSI PENJUALAN, DAN KUALITAS PELAYANAN ELEKTRONIK TERHADAP MINAT BELI ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Studi pada Konsumen Tokopedia di Semarang) - Puspita, Dinda Ayu; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The rapid development of technology, communication and information in the world makes a business have to adapt to technological changes, one of which is utilizing the internet with E-commerce. E-commerce can contribute to UMKM’s such as expanding market share, reducing operational costs such as shop rental costs, marketing and logistics costs, and others. The high growth of e-commerce in Indonesia increases opportunities while tightening competition. One of the developing e-commerce in Indonesia is Tokopedia. Tokopedia is always in the first rank of e-commerce that is frequently visited every month and always gets the Top Brand title at the Top Brand Award event. Even though it always gets the title of Top Brand, Tokopedia still can't be in the first position. Even in 2019 and 2020 Tokopedia's Top Brand Index (TBI) decreased. Tokopedia is also suspected of experiencing a decrease in Minat Beli Ulang as indicated by a decrease in the number of visitors to their website. In addition, tthere are still many complaints from consumers who have shopped at Tokopedia. This study aims to determine and analyze the effect of Perceievd Ease of Use, Sales Promotion, and E-Service Quality on Repurchase Intention by using Customer Satisfaction as a mediating variable for Tokopedia consumers in Semarang. The sampling technique used was nonprobability sampling with purposive sampling as the sampling method. The number of samples used in this study were 125 respondents with criteria including respondents having made a purchase at Tokopedia at least once, domiciled in Semarang City, and aged 17-58 years. The research data was obtained by distributing questionnaires online via the Google form. There are four hypotheses in this study which were analyzed and tested using the Structural Equation Modeling (SEM) analysis technique, using the Analysis of Moment Structure (AMOS) program. The results of testing the four proposed hypotheses show that the four hypotheses are accepted, namely Perceievd Ease of Use has a positive and significant effect on Customer Satisfaction, Sales Promotion has a positive and significant effect on Customer Satisfaction, E-Service Quality has a positive and significant effect on Customer Satisfaction, and Customer Satisfaction has a positive and significant effect on Repurchase Intention.